Predictors of cognitive enhancement after training in preschoolers from diverse socioeconomic backgrounds - Segretin, María Soledad; Lipina, Sebastian J.; Hermida, María Julia; Sheffield, Tiffany D.; Nelson, Jennifer M.; Espy, Kimberly A.; Colombo, Jorge A. (Frontiers in Psychology, 2014)
The association between socioeconomic status and child cognitive development, and the positive impact of interventions aimed at optimizing cognitive performance, are well documented. However, few studies have examined how specific socio-environmental factors may moderate the impact of cognitive interventions among poor children. In the present study, we examined how such factors predicted cognitive trajectories during the preschool years, in two samples of children from Argentina, who participated in two cognitive training programs between the years 2002 and 2005: the School Intervention Program (SIP; N=745) and the Cognitive Training Program (CTP; N=333). In both programs children were trained weekly for 16 weeks and tested before and after the intervention using a battery of tasks assessing several cognitive control processes (attention, inhibitory control, working memory, flexibility and planning). After applying mixed model analyses, we identified sets of socio-environmental predictors that were associated with higher levels of pre-intervention cognitive control performance and with increased improvement in cognitive control from pre- to post-intervention. Child age, housing conditions, social resources, parental occupation and family composition were associated with performance in specific cognitive domains at baseline. Housing conditions, social resources, parental occupation, family composition, maternal physical health, age, group (intervention/control) and the number of training sessions were related to improvements in specific cognitive skills from pre- to post-training.